Successful Investment Strategies of Sovereign Wealth Funds in the Global Economy: The Case of SOFAZ (State Oil Fund of the Republic of Azerbaijan - Damirli Mammadzada, Fatima; Aghabeyli, Firuza; Ibrahimli, Fidan (My University, 2026)
The objective of the paper is to conduct an assessment of investment practices and sustainability considerations of the State Oil Fund of the Republic of Azerbaijan (SOFAZ) given the rise in fiscal pressures and the changing trends in the global economy. The Fund plays an important role in the administration of oil/gas revenues, maintaining economic stability, and ensuring future wealth. However, the simultaneous increase in budget payments and decline in oil revenues pose questions about the sustainability of the fund. This study intends to explore the ability of the current management and investment strategy of SOFAZ to satisfy both short-term financial needs and the country's wealth in the long term. To analyze the issue, a qualitative research approach will be used based on the collection of data from reports, academic literature, and semi-structured interviews. Furthermore, there are some comparisons provided with other sovereign wealth funds around the world. It turns out that increased state budget payments and lower hydrocarbon revenues may limit the fund's potential investment capabilities and pose additional threats in times of economic uncertainties. The study emphasizes the need for better governance, sustainable transfer mechanism, and prudent fiscal policy.
Keywords: sovereign wealth funds; fiscal policy; SOFAZ; investment strategy; portfolio